SMAQ a measurement-based tool for traffic modeling and queuing analysis. II. Network applications. - Li, San-Qi
For pt. I see ibid. p.56-65 (1998). SMAQ is a measurement-based tool for integration of traffic modeling and queuing analysis. It can be used in a variety of network design areas. For instance, it can be used as a traffic generator to generate various traces for network testing. It also provides numerical solutions of the queue length and loss rate performance for transport of multimedia traffic. Several application modules are built into the tool for the evaluation of statistical multiplexing, buffer dimensioning, and link bandwidth allocation. Other examples include the evaluation of traffic shaping, local-congestion control, and the modeling of wireless channel dynamics. As one will find, the SMAQ tool indeed provides a solution technique for network engineers to solve many of the current design issues
Keywords: SMAQ; Application modules; Buffer dimensioning; Link bandwidth allocation; Local-congestion control; Loss rate performance; Measurement based tool; Multimedia traffic; Network applications; Network design; Network testing; Numerical solutions; Queue length; Queuing analysis; Software tools; Statistical multiplexing; Traffic generator; Traffic modeling; Traffic shaping; Wireless channel dynamics modelling